Three new species of the tribe Meconematini (Orthoptera: Tettigoniidae) from Taiwan - Lin, Changyan; Cui, du Xi; Ming, Shi Fu (Zootaxa, 2013)
The paper reported three new species from Taiwan, i.e. Xizicus (Eoxizicus) taiwanensis sp. nov., Xizicus (Axizicus) falcata sp. nov. and Decma (Decma) brachyptera sp. nov., supplied the descriptions and illustrations.